Multifunctionality of an Urbanized Coastal Marine Ecosystem - Archana, Anand; Baker, David Michael (Frontiers in Marine Science, 2020)
Coastal marine ecosystems provide numerous invaluable services and benefits to humankind. However, urbanization of coastal areas has homogenized and reduced the biodiversity of the surrounding marine environment and the sustainability of the multiple ecosystem services it provides. Studies have focused on single ecosystem functions despite human populations relying on several functions being delivered at once (known as multifunctionality). This study investigates five ecosystem functions (primary productivity, herbivory, predation, organic matter decomposition and carbon sequestration) and overall multifunctionality in four sites along a gradient of 16 environmental parameters. Ecosystem function varied significantly between sites that were farthest apart. In determining factors that drove ecosystem functioning, we found a positive relationship between coral cover and primary productivity but negative relationships between coral cover and levels of herbivory and predation intensity. Higher temperatures and greater concentrations of chlorophyll-a had a positive impact on predation and herbivory respectively. Notably, we found a significant negative impact of total inorganic nitrogen and significant positive impact of total Kjeldahl nitrogen on carbon sequestration. Further, individual functions were compared with fish abundance (obtained from seawater eDNA), and benthic community composition (obtained from plate % coverage of autonomous reef monitoring structures). Increasing herbivorous fish abundance had a positive impact on Ulva mass loss. Overall, relative abundance of predatory, omnivorous and planktivorous fish exerted overriding influences on primary productivity and predation intensity, implying that fishing pressure and marine protected area status are important factors. Importantly, we found significant effects from environmental parameters indicating that reliably predicting the effects of future anthropogenic impacts will not be straightforward as multiple drivers are likely to have complex effects. Taken together, urbanized coastal ecosystems exhibit varying levels of multifunctionality depending on the extent of human impact, and the functional diversity of the benthic community present.